METHODS OF MEASURING THE TIME OF RELAXATION OF NEOGENE AND CARBONIFEROUS RESERVOIR ROCKS GAS AND OIL FIELDS BY NUCLEAR MAGNETIC RESONANCE METHOD - Fedoryshyn, D.; Trubenko, A.; Fedoryshyn, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of study of nuclear-magnetic parameters for productive gas-saturated reservoir rock of the Neogene deposits at gas and gas condensate fields of the Bilche-Volytska zone Precarpathian Foredeep are considered in the paper. The correlation of physical and petrophysical parameters between the nuclear-magnetic parameters for reservoirs of the Neogene deposits Bilche-Volytska zone Precarpathian foredeep is shown. The dependence of the change of free fluid index on shaliness is established. The influence of rocks surface activity on their relaxation characteristics of Neogene and Carboniferous deposits is revealed and grounded. The established connection is obtained by comparing the reduced capacity of the cation exchange gп and the hygroscopic moisture Wг with the velocity of longitudinal relaxation (1 / T1).
Keywords: rock-collector; free fluid index; nuclear-magnetic parameters; relaxation characteristics; relaxation time